2003
DOI: 10.1124/jpet.102.048603
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Action of Itopride Hydrochloride on Colonic Motor Activity in Vitro and in Vivo

Abstract: We investigated the effects of itopride hydrochloride (itopride,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 21 publications
(17 reference statements)
3
34
1
6
Order By: Relevance
“…On the other hand, itopride hydrochloride is a benzamide derivative and acts through both dopamine D2 receptor antagonism and acetylcholinesterase inhibition. Previous studies have revealed that itopride hydrochloride stimulates the colonic peristalsis with propelling colonic luminal contents [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, itopride hydrochloride is a benzamide derivative and acts through both dopamine D2 receptor antagonism and acetylcholinesterase inhibition. Previous studies have revealed that itopride hydrochloride stimulates the colonic peristalsis with propelling colonic luminal contents [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Mosapride did not affect the colonic motor index in conscious dogs, and showed a relatively high EC50 value, indicating low affinity for the distal colon in guinea pig (Mine et al, 1997). In the isolated guinea pig colon, mosapride augmented only segmental contraction in the proximal portion, and failed to induce peristaltic acceleration (Tsubouchi et al, 2003). However, mosapride increased the amplitude of proximal colonic motility in conscious guinea pigs, measured by a force transducer recording contractions of the circular muscle of the proximal colon (Inui et al, 2002).…”
Section: The Effect Of 5-ht4 Receptor Agonists On Colonic Motor Functionmentioning
confidence: 95%
“…На сегодняшний день получены экспериментальные данные о стимулирующем влиянии итоприда на моторику кишечника [63]. Представляется перспективным приме-нение итоприда гидрохлорида у пациентов с хрониче-ским дуоденитом и явлениями дуоденостаза [64,65].…”
Section: результаты многочисленных международных и российских исследоunclassified